Pulmonary aspiration occurring during the induction of anesthesia in a patient with esophageal dilatation - Lim, Hyun Kyoung; Lee, Mi Hyun; Jin, Chan Ik; Byeon, Hyo Jin; Song, Jang Ho (Korean journal of anesthesiology, 2013)
KCI Citation Count: 1